Rebranding Bandung Makuta Melalui Media Sosial Instagram - malahayati, erfinna ardia; Mukarom, Zaenal; Risdayah, Enok (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This study aims to determine the process of Bandung Makuta’s rebranding activities carried out through social media Instagram using the concept initiated by Muzellec and Lambkin through four stages of rebranding. This study was conducted using a case study method with primary and secondary data obtained through in-depth interviews, observation, and documentation. The results of the study show that in its rebranding activities, Bandung Makuta can build an expansion of market segmentation through four rebranding stages: 1) Renaming, naming a new business unit "Makuta retail" 2) Repositioning, expanding market segmentation 3) Redesigning, changing design concepts, and 4 ) Relaunching, publication of new product launches. The four stages carried out by Bandung Makuta in the rebranding process are carried out as a product diversification process to attract consumer interest and generate other income. Some of the stages in the rebranding process can be said to be quite effective, but there are shortcomings in the final stage of the rebranding activity, namely relaunching.